Interactive reading opportunities beyond the early years: What educators need to consider - Merga, Margaret (Sage Publications Ltd., 2017)
© 2017, © Australian Council for Educational Research 2017. While the benefits of interactive reading opportunities, such as reading aloud and being read to, are well established, little is known about children’s attitudes toward, and perceptions of these practices beyond the early years. Research in this area can inform literacy instruction aimed at encouraging enjoyment and continuance of this practice. The 2016 Western Australian Study in Children’s Book Reading explored the attitudes of children aged 8–11 toward infrequency and cessation of interactive reading, their experiences of interactive reading with siblings, and the social and emotional effects that they felt listening to reading had on them. Children also described what they learned from listening to reading and reading aloud, as well as their attitudes toward reading aloud at school. Interactive reading experiences are complex and diverse social and educational events, with opportunities for shared reading experience related to growth in skill and confidence, and early cessation at home and at school heightening anxiety toward reading aloud.